Cast in a Racial Mould Labour Process and Trade Unionism in the Foundries - Webster, Edward (Wits University Press, 2025)
A groundbreaking study examining worker resistance in South Africa's metal industry, analyzing how racial dynamics shaped labour control in foundries and how black workers' resistance transformed industrial relations, challenging both traditional craft privileges and state attempts at incorporation